2020
DOI: 10.3390/plants9111589
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exogenous Salicylic Acid on Drought Response and Characterization of Dehydrins in Impatiens walleriana

Abstract: Impatiens walleriana is a valued ornamental plant sensitive to drought stress. We investigated whether the foliar application of 2mM salicylic acid (SA) can protect potted I. walleriana plants from drought stress. The plants were divided into: watered plants, drought-stressed plants, watered plants treated with SA and drought-stressed plants treated with SA. The number of flowers and flower buds, relative water content (RWC), contents of malondialdehyde (MDA) and proline (Pro) and the activities of superoxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…3A), as SOD is known to catalyze the dismutation of [56,57]. It has also been reported that foliar application of SA improved the expression of SOD encoding gene Cu/ZnSOD in Impatiens walleriana plants under drought stress [58]. CAT, APX and POD are involved in the detoxification of H 2 O 2 [59].…”
Section: Discussionmentioning
confidence: 98%
“…3A), as SOD is known to catalyze the dismutation of [56,57]. It has also been reported that foliar application of SA improved the expression of SOD encoding gene Cu/ZnSOD in Impatiens walleriana plants under drought stress [58]. CAT, APX and POD are involved in the detoxification of H 2 O 2 [59].…”
Section: Discussionmentioning
confidence: 98%
“…Reduced leaf area and accumulated ABA contributed to reduction of transpirational water loss in drought-stressed I. walleriana, while the activity of antioxidants had an important role in neutralizing oxidative stress [ 3 ]. In order to increase drought tolerance in I. walleriana, salicylic acid was exogenous applied, and its effects on growth and development have been assessed by our research team [ 47 , 48 ]. Analysis of aquaporins gene expression indicated a very important role of these proteins in water transport in plants during drought [ 49 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aquaporins sequences were obtained from sequenced I. walleriana transcriptome (RNA-seq). Details about transcriptome sequencing have been previously described [ 3 , 48 ]. To identify aquaporin sequences in I. walleriana, the leaf transcriptome annotated by Trinotate [ 3 , 48 ] was searched for PFAM accession and Interpro accession IPR000425.…”
Section: Methodsmentioning
confidence: 99%
“…In other plants such as papaya, drought stress followed by rewatering induced changes in hormonal levels, specifically jasmonic acid (Mahouachi et al, 2007 ). In other plants, the role of salicylic acid in alleviating water stress and inducing antioxidant enzymes has been shown (Antonic et al, 2020 ; Wakchaure et al, 2020 ). In this system, rehydration stress following dehydration also involved the induction of gene expression related to jasmonic acid, salicylic acid, and antioxidative systems ( Supplementary Table 2 ).…”
Section: Discussionmentioning
confidence: 99%